(untitled) (Research, Society and Development, 2022)
Brazil is today a major agricultural producer, with great emphasis on the production of harrows, and intensive use in technological innovation, being the largest soybean producer in the world, having already managed to surpass the United States in 2020 with a production of 82 million tons. In this context, the present work contributes to the discussion about soy in Brazil, which aimed to verify the sustainability of soy in our country, making a comparison between the texts related to the process and commercialization of soy with the theory of sustainability, the Triple Botton Line, created by John Elkington in 1994, which analyzes the business through the prism of the economic, social and environmental pillars. It can be concluded that from an economic point of view, soybean farming contributes positively. From a social point of view, the contribution to sustainability is small and the environmental issue is the biggest concern of specialists, since soy always needs more land and there is a fear of deforestation.